Quantification of metal release from stainless steel electrodes during conventional and pulsed ohmic heating - Pataro, Gianpiero (2014)
Electrochemical reactions at the electrode-solution interface of an ohmic heater can be avoided or significantly limited by choosing appropriate processing conditions in relation to the food properties. In the present work the effect of the electrical parameters (electric field strength and frequency of the applied current signal) and product factors (halides concentration, electrical conductivity and pH) on metal release from stainless steel (type AISI 316 L) electrodes of a batch ohmic heater was investigated. In each experiment, the concentrations of the main constituents of stainless steel (iron, chromium and nickel) released in the heating medium were detected by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) and Atomic Absorption Spectrophotometry (AAS). Results showed that the rate of metal release from the electrodes to the heating medium depends on frequency and applied field strength. However, the use of ohmic heating at a higher frequency than conventional (50 Hz) can significantly (p ≤ 0.05) reduce the flux of metal ions from stainless steel electrodes. Moreover, it was also demonstrated that electrochemical phenomena occurring at the electrode-solution interface strongly depend on the composition, pH and electrical conductivity of the heating medium. Industrial relevance: The magnitude of electrode material released into the heating medium during ohmic processing depends on many factors, whose effects should be known in order to define optimal treatment conditions, electrode material and food properties able to avoid or minimize the undesired phenomenon of contamination of the food product, electrode-fouling and electrode corrosion. This paper contributes to clarifying the effects of electric field strength applied as well as electrical conductivity, pH, and presence of halides in the heating medium on electrode corrosion or release of electrode materials during high frequency (25 kHz, bipolar square wave) pulsed power OH in comparison with conventional (50 Hz sine wave) OH. Interestingly, the use of sufficiently large frequencies may avoid or reduce the extent of electrochemical reactions at the electrode interface, minimizing corrosion and leakage of metals to the heating medium, even when electrode material of low cost and electrochemically active like stainless steel is used.